2022
DOI: 10.3390/diagnostics12102300
|View full text |Cite
|
Sign up to set email alerts
|

Rare X-Linked Hypohidrotic Ectodermal Dysplasia in Females Associated with Ectodysplasin-A Variants and the X-Chromosome Inactivation Pattern

Abstract: The goal of this study was to identify the pathogenic gene variants in female patients with severe X-linked hypohidrotic ectodermal dysplasia (XLHED). Whole-exome sequencing (WES) and Sanger sequencing were used to screen for the pathogenic gene variants. The harmfulness of these variations was predicted by bioinformatics. Then, skewed X-chromosome inactivation (XCI) was measured by PCR analysis of the CAG repeat region in the human androgen receptor (AR) gene in peripheral blood cells. Two novel Ectodysplasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In 2004, a separate study in Korea also identified the mutation in a male proband, while the other members of this family were homozygous for the normal allele (Na et al, 2004). Interestingly, the variant c.1045G>A (p.A349T) was found to cause XLHED in a Chinese female carrier who exhibited XLHED traits such as lack of teeth, sparse eyebrows, hypohidrosis, and some other facial abnormalities (Haochen Liu et al, 2022). This female patient was determined to have significant skewed X-chromosome inactivation (XCI) with a ratio of 98:2.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2004, a separate study in Korea also identified the mutation in a male proband, while the other members of this family were homozygous for the normal allele (Na et al, 2004). Interestingly, the variant c.1045G>A (p.A349T) was found to cause XLHED in a Chinese female carrier who exhibited XLHED traits such as lack of teeth, sparse eyebrows, hypohidrosis, and some other facial abnormalities (Haochen Liu et al, 2022). This female patient was determined to have significant skewed X-chromosome inactivation (XCI) with a ratio of 98:2.…”
Section: Discussionmentioning
confidence: 98%
“…This female patient was determined to have significant skewed X-chromosome inactivation (XCI) with a ratio of 98:2. However, the particular mechanism of skewed XCI to cause XLHED in female patients was not clear, as its consequences vary among different female carriers (Haochen Liu et al, 2022). Since the variant c.1045G>A (p.A349T) has been detected recurrently in several distinct patients with different ethnicities, it might be a mutational hot spot.…”
Section: Discussionmentioning
confidence: 99%